2020
DOI: 10.7759/cureus.10264
|View full text |Cite
|
Sign up to set email alerts
|

The Possibility and Cause of Relapse After Previously Recovering From COVID-19: A Systematic Review

Abstract: The severe acute respiratory distress syndrome coronavirus-2 (SARS-Cov-2) is a novel coronavirus that is believed to be mainly transmitted via droplet and contact transmission. While research is focusing on epidemiology, transmission, vaccine development, and therapeutics for coronavirus disease 2019 (COVID-19), there is a possibility of disease relapse. There are reports of patients who tested positive for SARS-Cov-2 after clinical recovery and initial clearance of the virus. Objective This systematic review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…One of these focused on the relapse of the disease, which is one of the potential causes of repeated positivity. It is noteworthy that none of the patients included in this study were asymptomatic at the time of relapse, which could act well to differentiate between reinfection and relapse [ 20 ]. In accordance, another study of 182 patients reported that repeated positivity during isolation after the initial episode of infection is rarely associated with the recurrence of disease if symptoms are absent [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of these focused on the relapse of the disease, which is one of the potential causes of repeated positivity. It is noteworthy that none of the patients included in this study were asymptomatic at the time of relapse, which could act well to differentiate between reinfection and relapse [ 20 ]. In accordance, another study of 182 patients reported that repeated positivity during isolation after the initial episode of infection is rarely associated with the recurrence of disease if symptoms are absent [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Immune response is the body's response to viral infection. Macrophages, neutrophils and dendritic cells produce a nonspecific innate response that slows the virus' progress and may even prevent the virus from causing symptoms [142] . After this non-specific response, the body will generate an adaptive immune response that specifically binds to the virus, and the adaptive response of this combination may clear the virus from the body [141] .…”
Section: Discussionmentioning
confidence: 99%
“…Although six systematic reviews and/or meta-analyses have been already published [ 142 , [151] , [152] , [153] , [154] , [155] ], none of them were comprehensive in terms of literature search. For example, one systematic review did not report the results of a systematic search, the number of included studies was uncertain [151] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results show that late asymptomatic RT-PCR re-positivity does occur after COVID-19, even 6 months later, and does not necessarily represent new infection, despite the prolonged time interval elapsed and the negativity of subsequent RT-PCR tests since the first diagnosis. Although asymptomatic and symptomatic SARS-CoV-2 re-positivity had been reported, median time to recurrence was usually lower, around 1-2 months [ 6 , 7 ]. We found that the CDC criteria showed to satisfactorily predict reinfection, since none of patients not meeting the proposed criteria showed to be reinfected after genomic sequencing testing, while reinfection was actually confirmed in the suspected case according to criteria.…”
mentioning
confidence: 99%